(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the results of early care and feeding methods for preterm infants at the Neonatal care & treatment Center in the National Hospital of Obstetrics and Gynecology in 2021. Methods: A prospective descriptive cohort study of 189 infants with gestational age from 25 weeks to 32 weeks receiving postpartum care at the Neonatal care & treatment Center in the National Hospital of Obstetrics and Gynecology from 1/11 2020- 30/6/2021. Results:189 infants received digestible feeding for 1.1 ± 0.3 days and took 16.8 ± 4.8 days to regain birth weight. The growth velocity of the preterm infants was 14,7 ± 5,9 g/kg/day. 124/189 infants had PGF (65,61%). The rate necrotizing enterocolitis was 5.8%, only 1 infant died on discharge (0.5%). Conclusion: Feeding premature babies by enteral nutrition is safe, effective, with few complications and helps babies to regain to birth weight early.